In-situ Assessment of Natural Radioactivity Concentrations and Hazard Indicators in the Mining Area of Lalitpur, Nepal - Upadhyay, Devendra Raj; Adhikari, Pramod; Khatri, Bal Vikram; Tajudin, Suffian Mohamad; Kalakhety, Himali; Khanal, Raju (Journal of Institute of Science and Technology, 2024)
Urban construction materials predominantly originate from mining sites, raising concerns about the associated natural radioactivity and its potential health impacts. This work focuses on assessing the distribution of three natural radionuclides and associated radiological indicators in the South Lalitpur mining area in Nepal. A portable gamma spectrometer information system (PGIS-2) was employed for in-situ measurement of natural radionuclide concentrations. The mean activity concentrations of 238U, 232Th, and 40K were found to be 85.82 ± 40.63 Bq kg−1, 104.87 ± 30.42 Bq kg−1, and 1257.47 ± 304.36 Bq kg−1, respectively. Radiological hazard parameters were computed and compared with global averages, revealing a radium equivalent activity (Raeq) mean of 332.62 ± 63.08 Bq kg−1, slightly below the global average. The average absorbed gamma radiation dose rate in the air was 155.94 ± 29.09 nSv hr-1, over twice the world average. Indoor and outdoor annual effective dose rates, excess lifetime cancer risks, and annual gonadal dose equivalents were slightly higher than world averages. Additional radiological indices were computed, indicating that most estimated parameters exceeded global averages. Multivariate statistical analysis was applied to the dataset. The study suggests that in-situ measurements of these radiological parameters in mining areas are essential, as most mean values were above global averages, emphasizing the need for environmental safety and awareness in mining regions.